Konflik Sosial Dalam Novel The Mango Season Karya Amulya Malladi - Dwi Lakshono (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2022)
This research’s title is social conflict in mango season novel by Amulya Malladi. In this novel, Priya is described as a girl that has lived in United State for seven years to study. After finished the study she must come back to his country. Unwittingly, American lifestyle changed Priya’s point view to live. So, when she came back to India Priya conflict with his family because she has different point view among his family to the live. The research’s purpose is to describe social conflict that’s experienced by main character in mango season novel by using character’s theory based on Nurgiyantoro and conflicts’ theory based on Soekanto & Sulistyowati. This method’s research is descriptive qualitative according to moleong. The research’s subject is Amulya Malladi’s mango season. Sociology of literature is the approach of this research according to Damono to describe Priya’s conflict with his family. This research describes Priya’s conflict with his family; Priya with his grandfather, Priya with his aunt, Priya with his grandmother, and Priya with his mom.